Association of Urinary Phthalates with Self-Reported Eye Affliction/Retinopathy in Individuals with Diabetes: National Health and Nutrition Examination Survey, 2001–2010 - Manju Mamtani; Joanne E. Curran; John Blangero; Hemant Kulkarni (Journal of Diabetes Research)
Background. An epidemiological association between exposure to phthalates and type 2 diabetes (T2D) is known. However, the potential role of environmental phthalates in the complications of T2D is unknown. Methods. Using data from the National Health and Nutrition Examination Survey (NHANES) 2001–2010, we studied the association of 12 urinary phthalate metabolites with self-reported eye affliction/retinopathy in 1,004 participants with diabetes. Data from retinal imaging was used to validate this outcome. Independence of the phthalates→T2D association was studied by adjusting for age, sex, race, marital status, educational attainment, poverty income ratio, physical activity, glycated hemoglobin levels, total serum cholesterol, serum high-density lipoprotein cholesterol, serum triglycerides, blood pressure, duration of diabetes, total calorie intake, and obesity. Results. Self-reported eye affliction/retinopathy had 82% accuracy with Cohen’s kappa of 0.31 (p<0.001). Urinary mono-n-octyl phthalate (MOP) was independently associated with the likelihood of self-reported eye affliction/retinopathy in subjects with T2D after accounting for all the confounders. This significance of this association was robust to the potential misclassification in cases and controls of retinopathy. Further, a significant dose-response relationship between MOP and self-reported eye affliction/retinopathy was demonstrable. Conclusions. We show a novel epidemiological link between the environment and diabetic complications in NHANES 2001–2010 participants.